2015
DOI: 10.1038/aps.2015.24
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumor activities of active ingredients in Compound Kushen Injection

Abstract: Kushen (Radix Sophorae Flavescentis) has a long history of use for the treatment of tumors, inflammation and other diseases in traditional Chinese medicine. Compound Kushen Injection (CKI) is a mixture of natural compounds extracted from Kushen and Baituling (Rhizoma Smilacis Glabrae). The main principles of CKI are matrine (MT) and oxymatrine (OMT) that exhibit a variety of pharmacological activities, including anti-inflammatory, anti-allergic, anti-viral, anti-fibrotic and cardiovascular protective effects. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
136
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(145 citation statements)
references
References 29 publications
(31 reference statements)
2
136
0
Order By: Relevance
“…It contains alkaloids, flavonoids, saccharides, and organic acids [82] and is extracted from two medical herbs including Radix Sophorae flavescentis and Rhizoma Smilacis Glabrae [83]. It modulates immunity, decreases inflammation, relieves cancer pain, and, most importantly, has anti-neoplastic activity [83].…”
Section: Traditional Chinese Medicines (Tcms) As Anti-cancer Agentsmentioning
confidence: 99%
See 2 more Smart Citations
“…It contains alkaloids, flavonoids, saccharides, and organic acids [82] and is extracted from two medical herbs including Radix Sophorae flavescentis and Rhizoma Smilacis Glabrae [83]. It modulates immunity, decreases inflammation, relieves cancer pain, and, most importantly, has anti-neoplastic activity [83].…”
Section: Traditional Chinese Medicines (Tcms) As Anti-cancer Agentsmentioning
confidence: 99%
“…It contains alkaloids, flavonoids, saccharides, and organic acids [82] and is extracted from two medical herbs including Radix Sophorae flavescentis and Rhizoma Smilacis Glabrae [83]. It modulates immunity, decreases inflammation, relieves cancer pain, and, most importantly, has anti-neoplastic activity [83]. For example, CKI downregulates β-catenin through the Wnt signaling pathway, which in turn targets the oncogenes c-MYC and CyclinD1 [84], leading to suppression of MCF-7 cancer stem cell-like side population (SP) cells [85].…”
Section: Traditional Chinese Medicines (Tcms) As Anti-cancer Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, transarterial chemoembolization (TACE) is one of the preferred treatments for patients with PLC who are not suitable for surgery or postoperative recurrence. FFKS was extracted from the mixture of Sophora flavescens and Heterosmilacis Japonicae with the mass ratio of 7 than 3, Experimental studies showed that FFKS could inhibit tumor cell growth, alleviate pain, elevated white blood cell, anti-infection and protect the body immune function [2,3].Until now, Many clinical trials showed that FFKS-TACE can reduce the adverse reactions and improve quality of life for primary liver cancer (PLC). however, a multi-center, randomized, double-blind PlaceboControlled Trial of FFKS-TACE for Treatment of PLC have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…PBCRBS could ameliorate neurological function deficits, reduce volume of hematoma and volume of perihematomal edema, and lower mortality rate and dependency in comparison with Western conventional medication controls or placebo based on a Meta-analysis [8] . Wang et al summarized the recent investigations on the anticancer activities and possible molecular targets of the Compound Kusen Injection, and then hypothesized that altering gene regulation in several pathways including Wnt signaling pathway might be involved in the underlying mechanisms [9] . To summarize the targets distribution of Fangjis, Liu and Wang defined multiple modes of array-designed combination therapies of Fangjiomics, such as "magic shotguns", vertical, horizontal, focusing, siege and dynamic arrays according to hits on targets, pathways or networks [10] .…”
mentioning
confidence: 99%